2015
DOI: 10.3892/ol.2015.3221
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of primary disease for penile squamous cell carcinoma: A Surveillance, Epidemiology, and End Results database analysis

Abstract: Abstract. Current guidelines recommend penile sparing surgery (PSS) for selected penile cancer cases. The present study described the use of PSS in a population-based cohort, and also examined the role of PSS on penile cancer-specific mortality (PCSM). Data from the Surveillance, Epidemiology, and End Results (SEER) database were used to identify individuals that were diagnosed with penile squamous cell carcinoma between 1998 and 2009 and treated with surgery. Patients were sorted into two groups: Local tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
12
3
1
Order By: Relevance
“…26 Following a multivariable analyses, age younger than 65 years, African American descent, tumor size of less than 3 cm, and pathological stage disease of no higher than T1 were reported predictors for the use of local tumor excision as surgical treatment of the primary penile tumor as part of a penile-sparing approach. 26 The authors concluded that penile-sparing surgery is underutilized in the general population, and significant age and racial/ethnic disparities exist in its use. 26 Other studies have noted that the majority of pa- tients identified with penile SCC in the SEER data set were treated with surgical therapy, and a small percentage of patients received radiotherapy alone or as adjuvant therapy.…”
Section: Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…26 Following a multivariable analyses, age younger than 65 years, African American descent, tumor size of less than 3 cm, and pathological stage disease of no higher than T1 were reported predictors for the use of local tumor excision as surgical treatment of the primary penile tumor as part of a penile-sparing approach. 26 The authors concluded that penile-sparing surgery is underutilized in the general population, and significant age and racial/ethnic disparities exist in its use. 26 Other studies have noted that the majority of pa- tients identified with penile SCC in the SEER data set were treated with surgical therapy, and a small percentage of patients received radiotherapy alone or as adjuvant therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…24 Demographical, racial/ethnic, and socioeconomic disparities can influence the treatments offered for patients with penile cancer in different populations (Table 2). 25,26 Zhu et al 26 used data from SEER to identify individuals diagnosed with penile SCC from 1998 to 2009 and treated with either local tumor excision or partial or total penectomy for their primary tumor. Of the 1,292 eligible patients, 24.2% underwent local tumor excision for surgical treatment of penile cancer.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations